2013
DOI: 10.1371/journal.pone.0074714
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of High Quality DNA from Seized Moroccan Cannabis Resin (Hashish)

Abstract: The extraction and purification of nucleic acids is the first step in most molecular biology analysis techniques. The objective of this work is to obtain highly purified nucleic acids derived from Cannabis sativa resin seizure in order to conduct a DNA typing method for the individualization of cannabis resin samples. To obtain highly purified nucleic acids from cannabis resin (Hashish) free from contaminants that cause inhibition of PCR reaction, we have tested two protocols: the CTAB protocol of Wagner and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 16 publications
0
15
0
1
Order By: Relevance
“…In addition, we compiled homologous nucleotide sequences available from ncbi databases the majority of which came from published studies (Sirikantaramas et al 2004;Kojoma et al 2006;Taura, Sirikantaramas, Shoyama, Yoshikai, et al 2007;El Alaoui et al 2013;McKernan et al 2015;Onofri et al 2015;Weiblen et al 2015;Cascini et al 2019;Doh et al 2019). Based on preliminary analyses, some sequences described by (Cascini et al 2019) were found to have relatively high levels of ambiguous nucleotides, probably due to unspecific amplification of multiple genes or gene variants.…”
Section: Gene Sequence Variation and Potential Geographic Originsmentioning
confidence: 99%
“…In addition, we compiled homologous nucleotide sequences available from ncbi databases the majority of which came from published studies (Sirikantaramas et al 2004;Kojoma et al 2006;Taura, Sirikantaramas, Shoyama, Yoshikai, et al 2007;El Alaoui et al 2013;McKernan et al 2015;Onofri et al 2015;Weiblen et al 2015;Cascini et al 2019;Doh et al 2019). Based on preliminary analyses, some sequences described by (Cascini et al 2019) were found to have relatively high levels of ambiguous nucleotides, probably due to unspecific amplification of multiple genes or gene variants.…”
Section: Gene Sequence Variation and Potential Geographic Originsmentioning
confidence: 99%
“…“Drug‐type” and “fiber‐type” cannabis material was differentiated and quantitated through analysis of the THC acid synthase gene . Seized Moroccan cannabis resin in a case recently proved a source of DNA . Real‐time PCR has been used to detect and quantify cannabis DNA .…”
mentioning
confidence: 99%
“…The method we present has four indispensable advantages. First, the method does not require post‐PCR gel processing or follow‐up DNA sequencing or fragment analysis using a CE , as required in previous plant species identification methods, which allows identification of multiple species in under 2 h—and without additional steps that may lead to sample loss, mislabeling, or contamination. Second, the method is cheaper than previous assays , as it requires no expensive dye‐labeled primers.…”
mentioning
confidence: 99%
“…The quantity and purity of the obtained DNA are similar to those obtained with CTAB protocols from young leaves and are, therefore, appropriate for molecular methods that require high‐quality DNA in abundant quantity. This method also represents an addition to other available methods for DNA extraction from other Cannabis samples, including those from leaves and resin (hashish) .…”
Section: Discussionmentioning
confidence: 99%